Task Followers and Labor Market Outcomes. - Chen, Liwen; Gordanier, John; Ozturk, Orgul (Journal of Labor Research, 2019)
This paper examines the extent to which children enter into occupations that are different from their father's occupation, but require similar skills, which we call task following. We consider the possibility that fathers are able to transfer task-specific human capital either through investments or genetic endowments to their children. We show that there is indeed substantial task following, beyond occupational following and that task following is associated with a wage premium of around 5% over otherwise identical workers employed in a job with the same primary task. The size of the premium is similar in magnitude to the size of the premium associated with occupational following. The wage premium is robust to controls for industry, occupation categories and occupation characteristics.